Konsep Diri dengan Kejadian Depresi pada Pasien Gagal Ginjal Kronik yang Menjalani Hemodialisa di RSUD Panembahan Senopati Bantul - Eka Nurul Fitriyani; Sri Arini Winarti; Sunarsih Sunarsih (JNKI (Jurnal Ners dan Kebidanan Indonesia) (Indonesian Journal of Nursing and Midwifery), 2014)
Kidney failure is a public health problem that is increasing every year. Patients with chronic renal failure always depended on dialysis machines, it may result a changes in their life as biological, psychological social, and spiritual changes. This condition may cause patient has negative self-concept such a nature inferiority, fear, anxious, even depression. The purpose of this study was to know relationship between self-concept and depression in patients who undergo hemodialysis at RSUD Panembahan Senopati Bantul. The study design was descriptive analytic with cross sectional. The samples were 61 respondents, it was selected by accidental sampling. The study instrument used questionnaire and analysis used was chi-square. The results showed that self-concept of patients with chronic renal was 67.2% negative, incidence of depression among patients who undergo hemodialysis was 82%. The chi-square test results obtained value of p 0.02 (<0.05). In conclusion, there was a relationship between self-concept and depression in patients with chronic renal failure who undergo hemodialysis.